Calculation of the Ecological Thresholds of Normal Pressure of Machine Propulsion Drive in Working on Clay Soils - A. N. Panasyuk; A. V. Lipkan (Сельскохозяйственные машины и технологии, 2020)
One of the conditions for achieving maximum land productivity is optimal soil density. In the Amur Region, ecological compaction thresholds for cereals are 1.0-1.24 grams per cubic centimeter, for soybeans – 1.09-1.25, which corresponds to a normal pressure of 80-120 kilopascals, depending on soil moisture. The authors showed that the tractors used in the Amur Region, acting on the soil, exceed the ecological compaction threshold. (Research purpose) To substantiate the ecological compatibility of mobile fi eld energy, primarily tractors engaged in fi eld work, in terms of the compacting eff ect from the normal load transmitted by their propulsion drive to the soil. (Materials and methods) The authors analyzed the experimental data on changes in density, hardness and resistance of soil to processing. An empirical dependence was obtained for calculating the increase in resistance to soil cultivation from the compaction load in a layer of 0-20 centimeters. (Results and discussion) The authors established an increase in plowing resistance of 12-25 percents at a normal load of 138-170 kilopascals, transmitted by the machine propulsion drive, which corresponded to a soil density of 1.25-1.30 grams per cubic centimeter; at a load of 180-250 kilopascals, the resistance increased by 43-50 percents which was equivalent to a soil density of 1.30-1.35 grams per cubic centimeter; at a pressure of 300-350 kilopascals, these indicators increased by 60-67 percents and up to 1.40-1.45 grams per cubic centimeter; and at 400 kilopascals, they showed an increase in resistance of 70-90 percents which is comparable to a density of 1.48 grams per cubic centimeter. (Conclusions) It was determined that the limit value of the normal pressure under the machine propulsion drive in fi eld work should be limited to 150-175 kilopascals. The ecological threshold of normal pressure was established – no more than 120-135 kilopascals with soil moisture of 20-23 percents which was comparable to the soil density of 1.2-1.25 grams per cubic centimeter. The limiting value of the normal pressure of the propulsion drive on the soil was calculated – 350 Pa, which corresponded to the critical soil compaction of 1.30 grams per cubic centimeter.